Brownson, Politics, and "The Laboring Classes" During a Presidential Election - Carey, Patrick W. (The catholic historical review, 2021)
A little more than three years before his conversion to the Catholic Church, Orestes Brownson wrote a radical essay on "The Laboring Classes." Brownson had a life-long sympathy for the poor working classes. His essay's Unitarian-Transcendentalist Christian arguments, and its proto-Marxist critique of the systemic evils of an economy that weighed heavily on the working class, created a widespread animated reaction in the political community during a presidential election, and eventually caused Brownson himself to rethink his own religious arguments.